Long-term add-on therapy (compassionate use) with oral artesunate in patients with metastatic breast cancer after participating in a phase I study (ARTIC M33/2) - Hagens, Cornelia von; Walter-Sack, Ingeborg; Goeckenjan, Maren; Storch-Hagenlocher, Brigitte; Sertel, Serkan; Elsässer, Michael; Remppis, Bjoern-Andrew; Munzinger, Judith; Edler, Lutz; Schneeweiss, Andreas; Strowitzki, Thomas (Phytomedicine, 2019)
BACKGROUND: The antimalarial artesunate (ART), a semisynthetic derivative of artemisinin from the Chinese herb artemisia annua has remarkable anticancer properties in vitro and in vivo. Its excellent safety profile known from short-term therapy in malaria was confirmed in an open phase I trial (ARTIC M33/2) for dose-finding as add-on therapy for four weeks. - PURPOSE: Patients with metastatic breast cancer, who had not experienced any clinically relevant adverse events (AE) during participation in ARTIC M33/2, were offered to continue ART as compassionate use (CU). Regular monitoring was continued in order to ensure adequate individual safety and tolerability and to collect information about long-term treatment with ART. Clinically relevant AEs or second progression of disease during ART were reasons for discontinuation of the add-on therapy. - STUDY DESIGN: Compassionate use was offered open-label to participants of ARTIC M33/2. - METHODS: Patients continued to take 100, 150 or 200mg oral ART daily as add-on therapy to their guideline-based oncological therapy. Clinical and laboratory monitoring included audiological and neurological examination, ECG, NTproBNP and reticulocyte determination. Cumulative treatment days and cumulative ART doses encompass both the phase I study as well as the continued add-on treatment period (CU). - RESULTS: Following the 4±1 weeks of the phase I trial, thirteen patients continued the add-on therapy as CU, resulting in a total of 3825 treatment days. In individual patients up to 1115 cumulative treatment days (37 months) and cumulative ART doses up to 167.3g were reached. A total of 25 AEs grade≥2 at least possibly related to ART long-term add-on therapy were documented, two, six and 17 in dose groups 100, 150 and 200mg/d ART respectively. Six of these AEs were classified as grade 3, two in patients taking 150 and four in patients on 200mg/d, none of them being probably or certainly related to ART. - CONCLUSIONS: In thirteen patients with metastatic breast cancer up to 200mg/d long-term oral ART (2.3-4.1mg/kg BW/d) in up to 1115 cumulative treatment days (37 months) did not result in any major safety concerns.
Gesehen am 03.04.2019